Domination Easymove Game on A Square Beehive - Baidari, Ishwar; Sajjan, SP (International Journal of Computer Sciences and Engineering, 2025)
This paper aims at circular chess on the new mode of playing board games by having an automated physical platform. Hence it discusses the development of an automatic chess board called as Chess. Which enables the user to play the game of chess in different formats with the opponents moves completely based user. It uses various types in graph sets the domination game played on a graph G consists of two players, Dominator and Staller, who alternate taking turns choosing a vertex of G such that whenever a vertex is chosen by either player, at least one additional vertex is dominated. Dominator wishes to dominate the graph in as few steps as possible and Staller wishes to delay the process The game domination number Gamma (G) is the number of vertices chosen when Dominator starts the game and the Staller as much as possible. Sushisen algorithms using game domination number Gamma’(G) when Staller starts the game. An imagination strategy is developed as a general Matlab tool for proving results in the domination game.